Edukasi Penggunaan Obat Saat Bulan Ramadhan Ditinjau dari Kesehatan dan Kaidah Islam di Lingkungan Warga Aisyiyah Kota Palangka Raya - Rabiatul Adawiyah; Agustinawati Umaternate; Risqika Yuliatantri Paramawidhita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Fasting is defined as worship holding back or abstaining from eating, drinking, and all things that cancel it, starting from dawn to sunset. Although obligatory, fasting has rukhsah (relief), which can be withdrawn, for example, in conditions that can endanger the safety of life or health if fasting is continued. Muslims who undergo fasting can have different medical conditions, for example, patients with hypertension, diabetes mellitus, peptic ulcer, gastroesophageal reflux disease, inflammatory bowel disease, lung disease, heart disease, kidney disease, and pregnancy. Therefore, knowledge of fasting and its effects on various medical conditions. Not many people understand very well about the rules of using drugs when fasting so that therapy does not go well, whereas illness that is not appropriately treated will disrupt our fasting. The solution offered is the existence of this service can provide an understanding to the citizens of Aisyiyah in the city of Palangka Raya about how to use drugs in the month of Ramadan in terms of health science and terms of Islamic principles.